f(x) = (x - 10)2 - 8
Simplifying f(x) = (x + -10) * 2 + -8 Multiply f * x fx = (x + -10) * 2 + -8 Reorder the terms: fx = (-10 + x) * 2 + -8 Reorder the terms for easier multiplication: fx = 2(-10 + x) + -8 fx = (-10 * 2 + x * 2) + -8 fx = (-20 + 2x) + -8 Reorder the terms: fx = -20 + -8 + 2x Combine like terms: -20 + -8 = -28 fx = -28 + 2x Solving fx = -28 + 2x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = -28x-1 + 2 Simplifying f = -28x-1 + 2 Reorder the terms: f = 2 + -28x-1